Faktor-faktor yang Mempengaruhi Ketepatan Penyaluran BOS Tingkat SDN DI Kabupaten Banjar - Yamin, Moh (Universitas Hamzanwadi, 2018)
This study aims to describe the factors that influences the accuracy of school operational fund towards the implementation of elementary education in Banjar regency. This research is descriptive and qualitative in which the questionnaire is the data collecting tool to find out the availability of acceptance, distribution mechanism, and realization of school operational fund program using prepared technical guidance. The samples are principals, teachers, school committees, and learners' parents in each district by purposive sampling technique. The results show that the acceptance and realization of school operational program in Banjar regency is in accordance with school operational fund technical guidance with some important notes where there are still school committees being lack of understanding of school operational fund technical guidelines; there are some management teams who are still having difficulty to manage the school operational fund program due to lack of understanding of technical guidances of operational school fund that often change and less master ICT, school operational fund amount insufficient for school operational requirement and for paying teacher honorarium; and there are still school components who feel receiving the donations of committees or parents' learners.